Effect of High-Flux versus Low-Flux Dialysis on the Rate of Bacteremia in Hemodialysis Patients: A Single Center Study (Journal of Renal and Hepatic Disorders, 2021)
Bacteremia in dialysis patients is a major risk factor of mortality. The aim of this study was to assess the effectiveness of dialysis with high-flux versus low-flux dialyzer regarding risk of bacteremia in dialysis patients. This was a retrospective cohort study that included dialysis patients who underwent dialysis therapy at old dialysis center where old low-flux dialyzers were used and the new dialysis center where high-flux dialyzers were used. The rate of positive culture was more in high-flux group (37.0%) compared to low-flux group (24.5%), although the difference was not statistically significant (P = 0.13). The vascular access was mostly permanent catheter in high-flux group compared to low-flux group (48.9% vs. 28.6%, respectively; P = 0.06), while arteriovenous (AV) fistula was more prominent in low-flux group compared to high-flux group (65.3% vs. 47.8%, respectively; P = 0.06). This was reflected in the type of bacteria, which was mostly from Gram-positive family (Staphylococcus). The results showed higher risk of bacteremia in high-flux group as compared to low-flux group; however, permanent catheters were more prominent in high-flux group.
Keywords: bacteremia; dialyzer; high flux; low flux